131 Zilpaterol Hydrochloride and Heat Stress Each Alter the Cattle Adipose Transcriptome and Predicted to Alter Molecular Pathways After 21 Days. (7th May 2021) - Reith, Rachel R; Sieck, Renae L; Grijalva, Pablo Cesar; Diaz, Duarte E; Schmidt, Ty B; Yates, Dustin T; Petersen, Jessica L
Abstract: Heat stress reduces livestock performance while supplementation of beta-adrenergic agonists (βAA) such as zilpaterol hydrochloride (ZH) improve production efficiency; both stimulate lipolysis. The objective of this study was to understand the effects (independent, interacting) of heat stress and ZH on the subcutaneous adipose transcriptome in fed steers. 24 Red Angus steers were assigned to thermoneutral (TN; THI=68) or heat stress (HS; THI=83) conditions and fed no supplement (NS) or ZH (8.33 mg/kg/day) for 21d in a 2x2 factorial. TN steers were pair-fed the HS daily average. Subcutaneous adipose samples were collected at day -3, 3, 10, and 21. RNA was isolated and sequenced using 3' Tag-Seq reads to a depth of 3.6 million reads/sample. Transcripts were mapped to ARS-UCD1.2 and quantified. After quality control, differential expression (DE) analyses were performed in DESeq2 with a significance threshold (FRD) of 0.05. Pathway analysis was used to explore pathways affected by HS, ZH, and their interaction using DE loci (P < 0.05). The acute phase response signaling pathway was predicted to be activated at 3d, but inhibited at 10d and 21d by the combination of HS and ZH. At multiple time points, inflammatory pathways including those for interferon and IL-8 were predicted to be activated by HS. Mitochondrial function pathways including oxidative phosphorylation, mitochondrial dysfunction, and TCA cycle II were altered by ZH. Adipose centric pathways for phospholipase-C and protein kinase-A signaling were altered by HS/ZH interaction while glycolysis was altered solely by HS. These data support the hypothesis that exposing cattle to HS conditions and ZH supplementation alters the subcutaneous adipose transcriptome, but not necessarily in an additive fashion. These data provide information regarding the supplementation of βAA in heat stress environments, especially if it mediates the effects of HS.